Ecological distribution of the shrimp Litopenaeus schmitti (Burkenroad, 1936) (Decapoda, Penaeoidea) in Ubatuba Bay, São Paulo, Brazil - Capparelli, Mariana V.; Kasten, Paula; Castilho, Antonio Leão [UNESP]; Costa, Rogério Caetano da [UNESP] (Int Science Services/balaban Publishers, 2012)
The penaeidean Litopenaeus schmitti, popularly known as white shrimp, is a species of great economic importance, being a target of fishing fleets in the southeast region of Brazil. It is distributed through the western Atlantic, from Cuba to Brazil, until Rio Grande do Sul. Adults are found from shallow depths up to 30 m and have been found to depths of 47 m in the state of Rio de Janeiro, while juveniles are located in bays and estuaries. The studied species is seasonally distributed in the region of Ubatuba. The objectives of this study are to analyze the abundance and ecological distribution of L. schmitti and to assess if and when juveniles use the Indaia estuary during their life cycle. Furthermore, the hypothesis was tested that the main period of recruitment in the bay coincides with the period of closure of fisheries defined by the Instruction of IBAMA. To that end, samples were taken monthly from July 2005 through June 2007, both in Ubatuba Bay and in the estuary formed by the Rio Indaia. At each sampling station, salinity, temperature (bottom), depth, organic matter content (%), and grain size of sediments were measured. We found that the largest catches in the estuary were in late spring and early summer. In Ubatuba Bay, peak catches occurred during winter and early spring, whereas in the second year, already in May, there was a high peak capture. The variation in the number of individuals was correlated with some environmental factors both in the estuary and in the inlet (p < 0.05). In the estuary, abundance was positively correlated with temperature (p = 0.008) and organic matter (p = 0.025) and negatively with depth (p = 0.009). Regarding the Ubatuba Bay, only temperature (p = 0.034) and depth (p = 0.013) were significantly associated with the distribution of the shrimp, both being negative relations. The shrimp L. schmitti uses both the estuarine as well the shore environment, particularly the Ubatuba estuary and its adjacent bay, to complete its life cycle. The proposed period of fisheries closure (between March to May in the state of São Paulo) for this and other shrimps coincides with individuals capable of reproduction entering the inlet and thus are being protected.
Keywords: White shrimp; Litopenaeus schmitti; Recruitment; Distribution; Size; Brazil